A MECHANISM FOR OPTIMIZING LOGISTICS COSTS IN THE PRODUCTION AND DISTRIBUTION SYSTEM OF A DAIRY INDUSTRY ENTERPRISE - Issayeva, Aiman; Turarov , Dauren; Arystambayeva, Almira; Dyrka, Stefan (Farabi Journal of Social Sciences, 2026)
Purpose. The purpose of this study is to develop and substantiate a mechanism for optimizing logistics costs in the production and distribution system of dairy industry enterprises, taking into account sector-specific characteristics and the asymmetric impact of key external and internal factors. Design/methodology/approach. The study is based on a systemic and process-oriented approach integrating diagnostic, analytical, managerial, and control-evaluation blocks. Logistics costs are classified according to functional, factor, and behavioral criteria. To quantify the influence of key determinants, autoregressive distributed lag (ARDL) and nonlinear ARDL (NARDL) models are applied, enabling the assessment of short-term and long-term relationships as well as asymmetric effects of fuel prices, electricity tariffs, and production volumes on logistics costs. Findings. The results reveal a stable long-term relationship between logistics costs and the selected factors. Logistics costs in the dairy industry demonstrate significant inertia and asymmetric sensitivity to changes in energy and fuel prices, with cost increases responding more strongly than cost reductions. The findings confirm that the highest optimization effect is achieved through targeted management of endogenous factors, particularly transport routing, energy efficiency of storage and production processes, and reduction of losses along the supply chain. Originality. The originality of the study lies in integrating a structured logistics cost classification with ARDL/NARDL-based econometric analysis into a comprehensive optimization mechanism tailored to the dairy industry, providing both theoretical contribution and practical applicability. Key words: logistics costs; dairy industry; supply chain management; ARDL/NARDL; cost optimization.